Checklist of ants of selected hill dipterocarp forests of peninsular Malaysia. - Nur Zati A.Mustafa; Lim , G.T; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2011)
A Survey of ants (Hymenoptera;formicidae) in six hill dipterocarp forests in peninsular Malaysia recorded 187 species (=morphospecies from seven subfamilies and 50 genera. Gunung Angsi forest reseach yielded the higher species richness (87 species).while Ulu Gombak forest reserve, the lowest(60 species)tewnty five genera were recorded for the subfamily myrmicinae, while the subfamilies ponerinae, formininae and dolichoderinae had 12,7 and 3 genera, respectively, cerapa aenictinae and psedomyricinae recorded one genus each.Myrmicines were the most speciose and abundant among the ant subfamilies,comprising 50.8% of total ant species and 50.6% of all ants collected, followed by ponerinae (21.4% and 35.7%),formicinae (17.6 and 11.6%)dolichoderinae (5.4%and 5.8 %),Aenictinae(2.1%and 0.2%),cerapachyinae(1.6% and 0.2%),and pseudomyrmininae(1.1%and 0.1% respectively).Pheidole was the most speciose genera, comprising 12.8% of ant species found.Lophomyrmes bedoti,odontoponera transversa,odontomachus rixosus, Diacamma scupturatum gnamptogenys modiglianii and unidentified species of pheidole,pachycondyla pheidolegeton and psedolasius were common species present in all the forest reserves sampled.